Vitamin D and GI cancers: shedding some light on dark diseases - Hargrove, Laura (AME Publishing Company, 2014)
Vitamin D synthesis and signaling affects numerous cellular processes including: proliferation, differentiation and apoptosis. It is now commonly recognized that low levels of vitamin D are associated with a greater risk of tumorigenesis. Cancers of the gastrointestinal tract are most often difficult to diagnose and treat as patients typically present with progressed disease. Basic research, clinical trials and population studies have supported the concept that treatment with Vitamin D may be a therapeutic option when treating GI cancers, however treatments must be individualized and monitored closely as the side effects from Vitamin D treatment can be increasingly harmful. This review will highlight the most recent findings regarding Vitamin D signaling and GI cancers.